2022
DOI: 10.1111/joa.13660
|View full text |Cite
|
Sign up to set email alerts
|

A new early hominin calcaneus from Kromdraai (South Africa)

Abstract: The Kromdraai fossiliferous site (26°00′41"S, 27°44′60″E) is one of the palaeokarsts truncated by surficial erosion, situated along the southern flank of the Blaauwbank River (Gauteng Province, South Africa). The Plio-Pleistocene site has borne many early hominin fossils and is listed among the UNESCO World Heritage Sites often referred to as the "Cradle of Humankind" (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
(244 reference statements)
0
7
0
Order By: Relevance
“…Changes in physical loadings and reduced mobility were previously reported for the populations inhabiting the Levant throughout the "Agriculture Revolution" (Eshed et al, 2004;May and Ruff, 2016). Hence, we hypothesized that calcaneal morphology would react to the changes in physical loadings applied to the bone, i.e., hunter-gatherers will have taller (MaxH) calcaneal tuber, taller (MinH) and wider (MinB) calcaneal body, wider distal calcaneus (LAW), and wider and longer dorsal articular surface (DAFB and DAFL) than later sedentary populations (Gierse, 1976;Su et al, 1999;Pablos et al, 2014;Harper et al, 2022b). However, the results only partially corresponded with our hypothesis (Figure 7).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Changes in physical loadings and reduced mobility were previously reported for the populations inhabiting the Levant throughout the "Agriculture Revolution" (Eshed et al, 2004;May and Ruff, 2016). Hence, we hypothesized that calcaneal morphology would react to the changes in physical loadings applied to the bone, i.e., hunter-gatherers will have taller (MaxH) calcaneal tuber, taller (MinH) and wider (MinB) calcaneal body, wider distal calcaneus (LAW), and wider and longer dorsal articular surface (DAFB and DAFL) than later sedentary populations (Gierse, 1976;Su et al, 1999;Pablos et al, 2014;Harper et al, 2022b). However, the results only partially corresponded with our hypothesis (Figure 7).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have also demonstrated differences in calcaneal morphology between populations having different lifestyles. Accordingly, hunter-gatherers or non-sedentary populations had taller and wider posterior calcaneus, wider anterior and middle talar facets, a protuberance on the dorsal aspect of the bone, and their internal structure included higher bone volume fraction than sedentary groups (Raichlen et al, 2011;Weiss, 2012;Hoover and Colette Berbesque, 2018;DeMars et al, 2021;Harper et al, 2022b;Harper, 2023). Furthermore, it has been suggested that additional factors affected calcaneal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The renewed excavations at Kromdraai since 2014 resulted in the in situ recovery of a new fossil hominin assemblage from Unit P [Braga et al, 2017[Braga et al, , 2021[Braga et al, , 2022a[Braga et al, ,b, 2023Harper et al, 2022]. The well preserved, though incomplete P. robustus infant mandible (KW 6420) (fig.…”
Section: A New P Robustus Juvenile Mandible From Kromdraai Unit Pmentioning
confidence: 99%
“…The renewed excavations at Kromdraai since 2014 resulted in the in situ recovery of a new fossil hominin assemblage from Unit P [Braga et al, 2017[Braga et al, , 2021Harper et al, 2022]. The well preserved, though incomplete P. robustus infant mandible (KW 6420) (fig.…”
Section: A New P Robustus Juvenile Mandible From Kromdraai Unit Pmentioning
confidence: 99%